San Francisco Gay Freedom Day Parade - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a caped snare drummer leading a group of San Francisco Gay Freedom Day Parade participants. Following him are individuals holding up posters. Left-to-right are poster images of Joseph Stalin, Adolph Hitler, Anita Bryant, Ku Klux Klan members with a burning cross, and Idi Amin.